Modelling of EM Wave Propagation in Distorted Conventional Optical Fiber to Multilayer Hollow Bragg Fiber - Narendra Bihari; Ritesh Kumar Chourasia (International Journal of Scientific Research in Science, Engineering and Technology, 2024)
Present investigation deals with the electromagnetic (EM) wave propagation through the asymmetrical (distorted) conventional optical fiber and extended the investigation for the distorted multilayered hollow Bragg Fiber. For this purposed theoretical and mathematical are well connected to investigate and further discuss the wave propagation through such distorted structure so that further many useful parameters like optical power, different losses, dispersion analysis, etc. can be computed easily by the researchers in the same area. In present study, the dispersion properties of an optical fiber with a little one-sided flattening are modelled using a straightforward mathematical approach that relies on coordinate transformation. In order to derive the modal eigenvalue equation, we provide the boundary condition under a weak guiding condition and choose new orthogonal coordinates that are suitable for the suggested waveguide construction. Further, a distorted Bragg fiber with a little flattened distortion is anticipated to have dispersion characteristics by comparing the fields at different boundaries.